Exploring the social innovation co-production nexus in Sofia: The case of Toplocentrala within the AGORA project - Mosquera Suarez, Jorge; Ostanel, Elena; Pagano , Giovanni (Tracce urbane. Rivista italiana transdisciplinare di studi urbani, 2023)
This paper investigates the territorial implications of social innovation and co-production of services in strategic spatial planning. It focuses on the regeneration of Toplocentrala, a socialist heritage building in Sofia that has been transformed into a regional centre for contemporary arts, within the context of the AGORA project’s strategic planning process. The research aims to enhance our understanding of the role of public action in social innovation and the need to redefine collaborative practices within institutional frameworks to promote innovation. A multi-method approach combining qualitative and quantitative data was employed, including site visits, interviews with key stakeholders, and secondary data analysis. The study highlights how strategic spatial planning processes involving social innovation and co-production of services can reshape the relationship between the state and civil society.